The Effects of Passion Fruit (Passiflora Edulis) Seed Extract For Health Benefit - Kristanti, Dea; Purnawati, Susy (Jurnal Penelitian Pendidikan IPA, 2023)
This study discusses the health benefits of the content of passion fruit (Passiflora edulis) seed extract. Google Scholar, Research Gate, and Mendeley were used as the search engine. The keywords were Passiflora edulis, passion fruit seed, antioxidant, and piceatannol. The benefits of passion fruit seed extract were analyzed from 21 articles. Twenty-one articles are used to demonstrate the health benefits of passion fruit (Passiflora edulis) seeds. The study's conclusions indicate that passion fruits may have anti-photoaging, anti-inflammatory, heart, liver, and kidney protective properties. They may also help treat skin conditions like striae distensae and acne vulgaris, as well as have anti-obesity, anti-hypertensive, anti-diabetic, anti-tumor, and anti-cancer properties. It is suggested where future research should go to improve the use of products made with passion fruits. It is hoped that more studies on the health benefits of passion fruit will be carried out using age-specific criteria, a larger sample size, and gender parity. Further prospective research is needed